3x2-23x-110=0 by using quadratic equation 

Posted by Yash Partap Singh (Jan 12, 2017 6:43 a.m.) (Question ID: 1302)

  • Add Comment
    Please Wait.. Editor is Loading..
  • Answers:
  • 3x2-23x-110=0

    3x2-33x+10x-110=0

    3x(x-11)+10(x-11)=0

    (x-11)(3x+10)=0

    x-11=0, 3x+10=0

    x = 11, -10/3

     

    Answered by Naveen Sharma (Jan 12, 2017 8:26 a.m.)
    Thanks (0)
  • Add Answer
    Please Wait.. Editor is Loading..

Sponsored Links

Download Mobile App

banner

Subscribe by E-mail

For Latest News and Updates from myCBSEguide.com
Enter your email address:

Join myCBSEguide

banner

Connect via Facebook

Sponsored Links